The devil's toy box : exposing and defusing Promethean terrorists - Fox, Andrew J. (Potomac Books, an imprint of the University of Nebraska Press, 2022)
Andrew Fox shows how to predict and assess the most dangerous terrorist threats likely to emerge in the near future in order to focus on countering them.